Emotional Education for the Development of Primary and Secondary School Students Through Physical Education: Literature Review - Sebastián Espoz-Lazo; Raquel Rodríguez Huete; Pablo Espoz-Lazo; Claudio Farías-Valenzuela; Pedro Valdivia-Moral (MDPI AG, 2020)
Emotions are embedded in the everyday life of every individual. In the same way their emotions are immersed in their cultural legacy, they are conditioned by behaviors that cannot be separated from an educational context. In this sense, physical education (PE) has been reported as a school subject that facilitates the emotional expression of primary and secondary school students. Thus, it seems to be important to understand how applied methodologies that enhance emotional education in this context help to develop students' skills regarding emotional management. In this context, 18 articles were selected from the Web of Science (WoS) under robust inclusion and exclusion criteria, which posteriorly were categorized and deeply analyzed. Results show that PE creates a favorable scenario for the expression of emotions. However, there is not sufficient evidence regarding emotional education methodologies that can be applied by PE teachers in their classes to improve primary and secondary students' management of emotions. It has been concluded that more proposals based on scientific evidence in this field are required.